Effectiveness as a method of learning from regulatory reality - Orozco Poveda, Daniela María; Hernández Tirado, Katerine (Revista Pedagogía Universitaria y Didáctica del Derecho, 2022)
This paper presents effectiveness as a pedagogical strategy that allows the study of law far beyond the traditional positive and dogmatic commitment and admits a teaching-learning process that leads to the interrelation between dogmatics, semiotics, and socio-political reality, which allows analyzing a living right and available to the service of the system to which it belongs. A holistic study is proposed from three approaches; that of the effectiveness of the legal norm from its capacity to produce legal effects, that of the effectiveness of the legal norm to motivate its application, and that of the effectiveness of the legal norm from the power that the norm has to generate symbols.